Photodisintegration cross section of deuteron - M, Odsuren; A.T, Sarsembayeva; G, Khuukhenkhuu; S, Davaa; K, Katō (Scientific transaction of the National University of Mongolia. Physics, 2022)
The peak produced by the M1 and E1 transition strengths for the photodisintegration cross section of deuteron is calculated in the complex scaling method and the origin of the peak of the M1 strength near threshold energy is discussed.